2022
DOI: 10.1007/s10928-022-09818-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of minimal physiologically-based pharmacokinetic-pharmacodynamic models for characterizing cellular kinetics of CAR T cells following local deliveries in mice

Abstract: Chimeric antigen receptor (CAR) T cell therapies have revolutionized the treatment of hematologic malignancies and have potentials for solid tumor treatment. To overcome limited CAR T cell infiltration to solid tumors, local delivery of CAR T cells is a practical strategy that has shown promising therapeutic outcome and safety profile in the clinic. It is of great interest to understand the impact of dosing routes on CAR T cell distribution, subsequent proliferation and tumor killing in a quantitative manner t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The quantitative correlation of the SCM and DM was not elucidated until our recent work (Li and Jusko, 2023), where we demonstrated how the number of liver sub-compartments (n) in the SCM correlated with the dispersion number (D N ) of the DM that describes the relative spread of solute on passage through the liver. We also showed that the SCM closely resembles the DM 9 (CAR) T cells (Tsai et al, 2022) and the PK of antenatal betamethasone and dexamethasone in parturient women and their fetuses (Krzyzanski et al, 2023).…”
Section: Introductionmentioning
confidence: 84%
“…The quantitative correlation of the SCM and DM was not elucidated until our recent work (Li and Jusko, 2023), where we demonstrated how the number of liver sub-compartments (n) in the SCM correlated with the dispersion number (D N ) of the DM that describes the relative spread of solute on passage through the liver. We also showed that the SCM closely resembles the DM 9 (CAR) T cells (Tsai et al, 2022) and the PK of antenatal betamethasone and dexamethasone in parturient women and their fetuses (Krzyzanski et al, 2023).…”
Section: Introductionmentioning
confidence: 84%
“…68 Interestingly, Tsai et al recently further adopted some features of the full PBPK/PD models to develop a minimal PBPK/PD model and characterized CAR-T distribution, proliferation, and tumor dynamics after local delivery of CAR-Ts for pleural and liver tumors in mouse models. 101 Although limitation exists due to key model assumptions and data requirement, such a modeling framework can further support the development of local delivery of CAR-Ts for solid tumors. Informed by the minimal PBPK/PD model, the authors suggested local delivery to be more effective for CAR-Ts in solid tumors as compared with systemic delivery.…”
Section: White Papermentioning
confidence: 99%
“…In addition to providing information on the in vivo expansion, persistence, efficacy, and safety, both immune‐compromised and immune‐competent mice may allow one to study the distribution and accumulation of the CAR‐T cells in different organs. This information may be used to advance previously developed in vitro ‐ based cell‐level models into semi‐mechanistic 65 or PBPK/PD models 30,59 …”
Section: Drug Developmentmentioning
confidence: 99%
“…46,57,58 Considering the manifold possibilities to influence the CAR-T cell phenotype (and with this the post-infusion expansion capacity) during CAR-T cell manufacturing, an abundance of options to combine design decisions regarding T cell activation, stimulation, expansion duration, and expansion conditions exist. Within an MIDD program, PBPK/quantitative systems pharmacology (QSP), 30,59 population PK/PD, 1,43,44,60 and emerging machine learning 22 approaches can be applied to incorporate the quantitative findings obtained in carefully chosen in vitro experiments investigating the impact of such design choices. The generated models can then be leveraged to perform hypothesis-generating simulations regarding the interactions of the actionable variables in the manufacturing phase, followed by model-informed design of the hypothesis-testing experiments.…”
Section: Cytokines In the Ex Vivo Expansion Mediummentioning
confidence: 99%
See 1 more Smart Citation